New water mites species (Acariformes: Hydrachnidia) from interstitial waters of the Russian Far East - Semenchenko, Ksenia A. (Zootaxa, 2016)
Illustrated descriptions of three water mite species, Wandesia sokolowi sp. n., Frontipodopsis cuspidata sp. n. and Chappuisides orientalis sp. n. from interstitial waters of the Russian Far East are presented. The male of Wandesia reducta Tuzovskij, 1987 is described for the ﬁrst time. An identification key of Russian species from the genus Wandesia, based on adults, is given.